Detection of Nocardia by 16S Ribosomal RNA Gene PCR and Metagenomic Next-Generation Sequencing (mNGS) - Ding, Juanjuan; Ma, Bing; Wei, Xupeng; Li, Ying (Frontiers in Cellular and Infection Microbiology, 2022)
In this study, the aim was to investigate the discriminatory power of molecular diagnostics based on mNGS and traditional 16S ribosomal RNA PCR among Nocardia species. A total of fourteen clinical isolates from patients with positive Nocardia cultures and clinical evidence were included between January 2017 and June 2020 in HeNan Provincial People’s Hospital. DNA extraction and 16S rRNA PCR were performed on positive cultures, and pathogens were detected by mNGS in these same samples directlyPCR primers were the bacterial 16S rRNA universal primer pairs, 7F and 1540R(5’ CAGAGTTTGATCCTGGCT3’, 5’AGGAGGTGATCCAGCCGCA3’), 27F and 1492R(5’ AGTTTGATCTTGGCTCAG 3’, 5’GGTTACCTTGTTACGACTT 3’). Among the 14 Nocardia isolates, four species were identified, and N.cyriacigeorgica (8 cases) is the most common species. Twelve of the 14 Nocardia spp. isolates were identified by the two methods, while two strains of N. cyriacigeorgica were not identified by mNGS. All tested isolates showed susceptibility to trimethoprim-sulfamethoxazole (SXT), amikacin and linezolid, but resistance to erythromycin. Apart from Nocardia species, other pathogens such as Acinetobacter baumannii, Klebsiella pneumonia, Aspergillus, Enterococcus faecalis, Human herpesvirus, etc., were detected from the same clinical samples by mNGS. However, these different pathogens were considered as colonization or contamination. We found that it is essential to accurately identify species for determining antibiotic sensitivity and, consequently, choosing antibiotic treatment. 16S rRNA PCR was useful for identification of nocardial infection among species, while this technique needs the clinicians to make the pre-considerations of nocardiosis. However, mNGS may be a putative tool for rapid and accurate detection and identification of Nocardia, beneficial for applications of antimicrobial drugs and timely adjustments of medication.